2002
DOI: 10.1113/eph8702350
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and Function of Somatic Primary Afferent Nociceptive Neurones with C‐, Aδ‐ or Aα/β‐Fibres

Abstract: Primary afferent neurones convey to the central nervous system information about the external and internal environments. They include low threshold neurones that respond to non-damaging, low intensity, stimuli and normally give rise to sensations other than pain, and high threshold or nociceptive neurones that respond to high intensity, potentially damaging stimuli and often result in a sensation of pain. This review will focus on somatic nociceptive afferent neurones, that is, those that project to the body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
216
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(238 citation statements)
references
References 0 publications
11
216
1
4
Order By: Relevance
“…With regard to these I K(Ca) blockers, apamin is a selective blocker of SK channels with IC 50 63 pM for the SK2, 2 nM for the SK3 subtype, and a range between 3.3 and 12 nM for SK1 [78]. Iberiotoxin selectively blocks BK channels with IC 50 in the low nM range [54], and clotrimazole blocks IK channels with IC 50 50 nM [22].…”
Section: Primary Afferent Neurons Express I K(ca)mentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to these I K(Ca) blockers, apamin is a selective blocker of SK channels with IC 50 63 pM for the SK2, 2 nM for the SK3 subtype, and a range between 3.3 and 12 nM for SK1 [78]. Iberiotoxin selectively blocks BK channels with IC 50 in the low nM range [54], and clotrimazole blocks IK channels with IC 50 50 nM [22].…”
Section: Primary Afferent Neurons Express I K(ca)mentioning
confidence: 99%
“…4-AP blocks delayed rectifier and A-type potassium channels [32] (IC 50 1-2 mM for various neuronal K+ channels [18,79,84]), glibenclamide selectively blocks ATP-sensitive K + channels [32] (IC 50 for inhibition of levcromakalim-activated current in adult rat intracardiac ganglionic neurons 55 nM [35]), and TEA blocks delayed rectifier, inward rectifier, A-type, BK and ATP-sensitive K + channels [32] (IC 50 in the low mM range for voltage-gated K+ currents in neurons [49], or in the 1-100 mM range for blocking various neuronal K + channels [41,67]). …”
Section: Recording Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Labeling with retrograde dyes injected into the target tissue has enabled characterization of functional attributes of the soma of nociceptors innervating those tissues. The heterogeneity of functional phenotypes observed in isolated sensory cell bodies (46,47) appears to reflect the variability observed in cutaneous nociceptor fiber types observed in studies in which recordings from fiber or soma during receptive field stimulation are combined with subsequent nociceptor labeling to identify terminal morphology (48,49) and the expression of nocisensors (50), markers, and peptides (48) ( Table 1). Nociceptors differentially express a variety of anatomical and biochemical markers (e.g., the expression of versican, the binding partner for the isolectin B4 [IB4]; ref.…”
mentioning
confidence: 99%
“…Many studies have addressed the question of correlations of action potential shape with sensory receptor functions (reviewed by Scott 1992;Lawson 2002). Although it has been suggested that differences in AP shape correlates with conduction velocity, evidence suggests a more important correlation with sensory function.…”
Section: Functional Relationships Associated With Tonic and Phasic Fimentioning
confidence: 99%